Finite element modelling and validation of the lubmar spine using a multi-block approach - Chua, Priscilla Tsie Hwee. (2012)
There is a growing trend in the use of computational biomechanical models in clinical studies, especially for analysing phenomena that cannot be clarified by experimental methods, thus the growing need to develop an accurate and reliable Finite Element model.